Prognostic relevance of tertiary lymphoid organs following neoadjuvant chemoradiotherapy in pancreatic ductal adenocarcinoma. Issue 6 (9th May 2019) - Kuwabara, Shota; Tsuchikawa, Takahiro; Nakamura, Toru; Hatanaka, Yutaka; Hatanaka, Kanako C.; Sasaki, Katsunori; Ono, Masato; Umemoto, Kazufumi; Suzuki, Tomohiro; Sato, Osamu; Hane, Yuma; Nakanishi, Yoshitsugu; et al.
Abstract: The efficacy of preoperative neoadjuvant chemoradiotherapy (NAC) in cases of pancreatic cancer with extremely poor prognoses has been reported. In this study, we aimed to identify novel biomarkers that reflect prognoses following chemoradiotherapy using tertiary lymphoid organs (TLO) expressed in the tumor microenvironment. Resected tumor specimens were obtained from 140 pancreatic cancer patients. We retrospectively investigated the clinical relevance of TLO by categorizing patients into those who underwent upfront surgery (surgery first [SF]) and those who received NAC. The immunological elements within TLO were analyzed by immunohistochemistry (IHC). In the IHC analysis, the proportions of CD8+ T lymphocytes, PNAd+ high endothelial venules, CD163+ macrophages and Ki‐67+ cells within the TLO were higher in the NAC group than in the SF group. In contrast, the proportion of programmed cell death‐1+ immunosuppressive lymphocytes within TLO was lower in the NAC group than in the SF group. The NAC group demonstrated favorable prognoses compared with the SF group. In the multivariate analysis, the TLO/tumor ratio was determined as an independent predictive prognostic factor. In conclusion, the administration of preoperative chemoradiotherapy may influence the immunological elements in the tumor microenvironment and result in favorable prognoses in pancreatic ductal adenocarcinoma patients. Abstract : The administration of preoperative chemoradiotherapy may influence the immunological elements in the tumor microenvironment and result in favorable prognoses in pancreatic ductal adenocarcinoma patients.